The Need Analysis of Ethno-Integrated Science Book Based on Pacu Jalur in Kuantan Singingi - Andika Febrian*; Zuhdan Kun Prasetyo; Suyanta Suyanta; Sri Rejeki Dwi Astuti; Nina Khaerunnisa (Universitas Syiah Kuala, 2023)
Currently science learning has several problems including the lack of contextual material discussed, thus making science learning considered less interesting, monotonous, and difficult. This study aims to analyze the need for science learning contents used in schools to solve those problem. The research method used is a qualitative type of survey research. Data collection techniques were carried out through interviews with science teachers, student questionnaires, scientific literacy tests, and observations. The number of samples was 3 teachers and 47 students through cluster random sampling. The instruments used in this study included interview guidelines, questionnaires, learning observation sheets, and scientific literacy tests. Data analysis in this study used descriptive qualitative. Based on this needs analysis, the results obtained recommend the development of integrated science textbooks containing cultural content on the Pacu Jalur Kuantan Singingi, to be able to increase scientific literacy and cultural concern of students